Assessment on connection between shallow and deep aquifers using isotope analysis of surface water and groundwater in Sunsari and Morang Districts - Neupane, Sharmila; Gajurel, Ananta Prasad; Shakya, Nir; Lupker, Maartin; Hada, Rabina (Journal of Nepal Geological Society, 2019)
The Sunsari and the Morang Districts confine the eastern region of the Koshi River and are considered as a huge potential of groundwater zones. The study mainly focuses on the concept of delineation of recharge source of groundwater and connection between aquifer system through isotopic analysis. Altogether 33 samples are collected from surface and groundwater for the isotopic analysis. Majority of the samples of flowing artesian wells are encountered under the range of -7.03‰ to -6.53‰. The shallow aquifers fall under the range of -5.94‰. to -5.34‰ and deep aquifers fall over a wide range of -7.13 ‰. to -6.53‰ for δ18O. Clustering of samples from isotopic analysis gives idea of surface water and groundwater interconnection along with the recharge source identification. Isotopic variation of majority of samples ranges from -7.34‰ to -4.74‰ while depleted value for δ18O is -10.16‰ in shallow aquifer of Jamungachhi, which indicates that the recharge source is precipitation at higher elevation. The d excess (greater than 10‰) concluded that the aquifer system in the study area is complex and recharged from various sources. The range of enrichment is measured as 2.6‰< 1.96‰<1.87‰<1.55‰ for shallow aquifers, rivers, deep aquifers and flowing artesian well. The significant increase in coarse particle towards the northern part reveals the good aquifer sequence in the northern zone and proves the best recharge area. The overall aquifer system in the study area is complex and recharged from various sources. Most of the aquifers are recharged from the river sand precipitation at higher altitude.